2014
DOI: 10.1038/ncomms6405
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative dual palladium/silver catalyst for direct difluoromethylation of aryl bromides and iodides

Abstract: Difluoromethylated arenes are one of the privileged structural motifs that are important for fine tuning the biological properties of drug molecules. No general catalytic method exists for the formation of difluoromethylarenes. Previous methods for the preparation of difluoromethylarenes typically required harsh conditions, multiple steps or stoichiometric amount of catalysts. Here we report a cooperative dual palladium/silver catalyst system for direct difluoromethylation of aryl bromides and iodides under mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(85 citation statements)
references
References 44 publications
(42 reference statements)
4
81
0
Order By: Relevance
“…Our initial efforts to synthesize (1 S )‐(–)‐ N ‐difluoromethylthio‐2,10‐ camphorsultam by reaction of (1S)‐(–)‐ N ‐chloro‐2,10‐camphorsultam with a combination of TMSCF 2 H and sulfur in the presence of various activators such as cesium fluoride or potassium tert ‐ butoxide were unsuccessful. Alternatively, reaction of (1 S )‐(–)‐ N ‐ chloro‐2,10‐camphorsultam with nucleophilic difluoromethylthiolating reagent [(SIPr)Ag(SCF 2 H)] (SIPr = 1,3‐bis(2,6‐di iso propyl phenyl) imidazolin‐2‐ylidene) did not generate the desired product. Finally, it was found that treatment of difluoromethanesulfenyl chloride, which was in situ generated from difluoromethyl‐benzylthioether with a solution of chlorine in chloroform, with the Oppolzer's sultam sodium salt at room temperature afforded reagent 9a after 5 h in 74% yield (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Our initial efforts to synthesize (1 S )‐(–)‐ N ‐difluoromethylthio‐2,10‐ camphorsultam by reaction of (1S)‐(–)‐ N ‐chloro‐2,10‐camphorsultam with a combination of TMSCF 2 H and sulfur in the presence of various activators such as cesium fluoride or potassium tert ‐ butoxide were unsuccessful. Alternatively, reaction of (1 S )‐(–)‐ N ‐ chloro‐2,10‐camphorsultam with nucleophilic difluoromethylthiolating reagent [(SIPr)Ag(SCF 2 H)] (SIPr = 1,3‐bis(2,6‐di iso propyl phenyl) imidazolin‐2‐ylidene) did not generate the desired product. Finally, it was found that treatment of difluoromethanesulfenyl chloride, which was in situ generated from difluoromethyl‐benzylthioether with a solution of chlorine in chloroform, with the Oppolzer's sultam sodium salt at room temperature afforded reagent 9a after 5 h in 74% yield (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the corresponding difluoromethylated products (palladium complexes or directly the organic molecules due to fast reductive elimination) were obtained in quantitative yields. With this fundamental knowledge in hand, the authors developed a catalytic difluoromethylation protocol of aryl halides (by using catalytic amounts of silver in the case of ref ), whereas in the case of heteroaryl halides fine‐tuning of the ligand (DPEPhos instead of XantPhos) was needed to obtain high yields of the corresponding organic products (Scheme b)…”
Section: Experimental Tools For Rational Designmentioning
confidence: 99%
“…6 In an effort to fulfill the ever-increasing demand [ for discovering new bioactive molecules, there are increasing requirements to synthesize diversified difluoromethylated structures in an efficient, straightforward, and economical way. In this context, tremendous efforts have been made in the catalytic synthesis of difluoromethylated arenes over the past decade [7][8][9][10][11][12][13][14] ; nonetheless, efficient and direct catalytic difluoromethylation processes of terminal alkynes remain elusive. We envisaged that since alkynes are a versatile building block in organic synthesis, 15 the connection with a CF 2 H to terminal alkynes would lead to a series of synthetically useful synthons for the construction of a wide range of difluoromethylated structures that would be of great interest in medicinal chemistry, chemical biology, and advanced functional materials.…”
Section: Introductionmentioning
confidence: 99%